2012
DOI: 10.1097/ccm.0b013e31825fd7da
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol improves myocardial ischemia and ischemic heart failure in mice by antagonizing the detrimental effects of fractalkine*

Abstract: Resveratrol alleviates the deleterious effects of fractalkine on myocardial ischemia and thus reduces subsequent cardiac remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 33 publications
2
49
0
Order By: Relevance
“…Furthermore, pretreatment of H9c2 cells with resveratrol prior to anoxia/re-oxygenation, reduced cell death in an AMPK and autophagy-dependent manner. Resveratrol was also shown to be protective in cardiomyocytes exposed to anoxia/reoxygenation through inhibition of fractalkine (FKN) [168], which was shown to inhibit the resveratrol-enhancement of autophagy in cardiomyocytes [168]. The roles of FKN and autophagy are important as it has been shown that autophagy is beneficial following MI due to a correction of the myocardial energy imbalance [192].…”
Section: Preclinical Studiesmentioning
confidence: 95%
See 2 more Smart Citations
“…Furthermore, pretreatment of H9c2 cells with resveratrol prior to anoxia/re-oxygenation, reduced cell death in an AMPK and autophagy-dependent manner. Resveratrol was also shown to be protective in cardiomyocytes exposed to anoxia/reoxygenation through inhibition of fractalkine (FKN) [168], which was shown to inhibit the resveratrol-enhancement of autophagy in cardiomyocytes [168]. The roles of FKN and autophagy are important as it has been shown that autophagy is beneficial following MI due to a correction of the myocardial energy imbalance [192].…”
Section: Preclinical Studiesmentioning
confidence: 95%
“…For instance, it has been shown that left ventricular systolic/diastolic function improved and infarct size was reduced in rats that received a daily administration of resveratrol 1 mg/kg for four weeks post-MI [167]. In addition, Xuan et al performed left coronary artery ligation on mice and found that resveratrol (20 mg/kg/day for 42 days) decreased cardiac remodeling and increased survival following the MI [168]. Similar positive results were observed in rats treated with 2.5 mg/kg/day resveratrol for 16 weeks post-MI [169].…”
Section: Preclinical Studiesmentioning
confidence: 96%
See 1 more Smart Citation
“…14,15 In rodent models, resveratrol has been shown to prevent and reverse cardiac remodeling. 16,17 It has been demonstrated that tropomyosin mutations are associated with abnormal calcium binding and ventricular remodeling. 18 We noted a significant decrease in tropomyosin 1 (alpha) and tropomyosin 2 (beta) in animals given resveratrol.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of platelet aggregation and a potential regeneration of tissue in the infarcted area are some RSV effects on myocardial ischemia (Raj et al., 2014). One of protective mechanisms by RSV in cardiomyocytes is induction of autophagy via SIRT‐1 and AMPK activation and inhibition of fractalkine protein as inhibitor of RSV‐induced autophagy (Xuan et al., 2012). Both antioxidant activity and increasing of nitric oxide bioavailability actions of RSV are required to exert its anti‐ischemic effects (Leikert et al., 2002).…”
Section: Resveratrol and Diseasesmentioning
confidence: 99%